Extraction and Purification of Antimicrobial Proteins from Datura Stramonium Seed - Muhammad, Surayya Mustapha; Sabo, Ibrahim A.; Gumel, Ahmed Mohammed; Alkali, Fatima I (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2019)
Resistant to antibiotics by microbes have become a major global challenge incurring economic and public health burden. Hence, research to develop new effective anti-biotics should be a major consideration to pharmaceutical industries, scientific researchers, Amanda ‘scientific researchers and world health organizations at large. This study is conducted to investigate the antimicrobial property of proteins present in the seeds of Datura stramonium. The extraction was carried out using Tris-HCL buffer prepared from 50M Tris and 0.3M NaCL, the proteins were isolated using ammonium sulphate precipitation to obtain 80% fraction. The isolated and extracted proteins sample were subjected to dialysis in which all the salt was removed and then purified using Ion-exchange chromatography. Acidic and basic fractions of the proteins obtained were subjected to SDS-PAGE electrophoresis to visualize their different molecular weight. More protein band was observed in the basic fraction between 9-45kDa. Antibacterial activities of both acidic and basic proteins were carried out using the paper disc diffusion method against clinical bacterial isolates of E. coli and Klebsiella pneumoniae. More activity was observed in basic protein with a diameter 8mm compared to the acidic fraction of 7mm in diameter.